Flattening filter for Gaussian‐shaped monochromatic X‐ray beams: an application to breast computed tomography. (27th January 2020) - Donato, Sandro; Arfelli, Fulvia; Brombal, Luca; Longo, Renata; Pinto, Andrea; Rigon, Luigi; Dreossi, Diego
Abstract : The presented parabolic‐shaped aluminum filtration system allows to flatten the Gaussian X‐ray intensity distribution produced by a bending magnet, resulting in more spatially homogeneous dose and image noise distributions, and to use a wider portion of the beam for imaging purposes. Abstract : The vertical intensity distribution of synchrotron‐based X‐ray beams usually has a Gaussian profile encompassing large intensity variations. For biomedical imaging applications this may entail sub‐optimal dose distributions and large fluctuations in terms of image noise. Commonly, planar metallic filters coupled with absorbing slits systems are applied to adjust the delivered flux and to limit intensity variations, respectively. The latter results in a reduction of the effective beam size. A flattening filter that counterbalances the transverse inhomogeneity, while retaining a sufficient flux, has been developed in the context of a monochromatic phase‐contrast breast computed tomography application, ongoing at the Elettra synchrotron facility. The implementation of the new filtration system results in homogeneous intensity (hence dose) distribution and signal‐to‐noise ratio across the imaged volume. Finally, and most importantly, it allows a wider portion of the beam to be used, directly translating into a major (∼40%) reduction of the overall scan time for samples requiring a field of view larger than the beam size ( i.e. multiple translation steps).